The Effects of Aerobic Exercise Training on Cerebrovascular and Cognitive Function in Sedentary, Obese, Older Adults - Bliss, Edward S.; Wong, Rachel H. X.; Howe, Peter R. C.; Mills, Dean E. (Frontiers in Aging Neuroscience, 2022)
and physical inactivity. This decline may be offset by aerobic exercise training (AT). We investigated the effects of 16 weeks AT on cerebrovascular and cognitive function in sedentary, obese, older adults. Twenty-eight participants were randomly allocated to AT or a control group. Before and after the intervention, transcranial Doppler ultrasonography was used to measure the cerebrovascular responsiveness (CVR) to physiological (hypercapnia, 5% carbon dioxide ) and cognitive stimuli. AT increased the CVR to hypercapnia (98.5 ± 38.4% vs 58.0 ± 42.0%, P = 0.021), CVR to cognitive stimuli (25.9 ± 6.1% vs 16.4 ± 5.4%, P < 0.001) and total composite cognitive score (111 ± 14 vs 104 ± 14, P = 0.004) compared with the control group. A very strong relationship was observed between the number of exercise sessions completed and CVR to cognitive stimuli (r = 0.878, P < 0.001), but not for CVR to hypercapnia (r = 0.246, P = 0.397) or total composite cognitive score (r = 0.213, P = 0.465). Cerebrovascular function and cognition improved following 16 weeks of AT and a dose-response relationship exists between the amount of exercise sessions performed and CVR to cognitive stimuli.